Phase Field Crystal Simulation of Grain Growth in BCC Metals during Additive Manufacturing. (23rd January 2017) - Ke, Hang; Mastorakos, Ioannis
ABSTRACT: In this work, we demonstrate that the phase field crystal (PFC) method can be applied to identify and predict the microstructure evolution during the solidification of the BCC metals in additive manufacturing. The results reveal the columnar structure of the grains, which matches the grain growth observed in real samples produced with the additive manufacturing technique. The effect of ambient temperature, seed-seed distance and seed-seed misorientation on the grain growth has been investigated. In addition, the formation of crystal defects during the process is recorded and the resulted long-range stresses are calculated using the eigenstresses theory.